2016
DOI: 10.1016/j.neo.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

miR-21, miR-155, miR-192, and miR-375 Deregulations Related to NF-kappaB Activation in Gastroduodenal Fluid–Induced Early Preneoplastic Lesions of Laryngeal Mucosa In Vivo

Abstract: Gastroduodenal refluxate found in the upper aerodigestive tract is not clinically uncommon. We recently demonstrated the neoplastic potential of gastroduodenal fluids (GDF) on hypopharyngeal mucosa, via NF-κB, using in vitro and in vivo models. Here we will explore the in vivo effect of GDF on laryngeal mucosa (LM) to induce early preneoplastic lesions related to NF-κB activation, along with deregulation of specific microRNA (miRNA) markers previously linked to laryngeal cancer. We used histological, immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(110 citation statements)
references
References 51 publications
10
98
2
Order By: Relevance
“…Others have shown that constitutive up‐regulation of miR‐155 may mediate prolonged inflammatory reactions leading to cancer 18, 52. We previously showed a significant up‐regulation of miR‐155 in laryngopharyngeal mucosa treated by acidic bile accompanied by pre‐neoplastic lesions 10. Our current findings show that BAY 11‐7082‐induced miR‐155 levels resulted in strong positive correlations with pro‐inflammatory TNF‐α, IL‐1β and ΙL‐6 mRNAs, suggesting a protective role of NF‐κB inhibition in pro‐inflammatory events linked to downstream oncogenic pathways.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Others have shown that constitutive up‐regulation of miR‐155 may mediate prolonged inflammatory reactions leading to cancer 18, 52. We previously showed a significant up‐regulation of miR‐155 in laryngopharyngeal mucosa treated by acidic bile accompanied by pre‐neoplastic lesions 10. Our current findings show that BAY 11‐7082‐induced miR‐155 levels resulted in strong positive correlations with pro‐inflammatory TNF‐α, IL‐1β and ΙL‐6 mRNAs, suggesting a protective role of NF‐κB inhibition in pro‐inflammatory events linked to downstream oncogenic pathways.…”
Section: Discussionmentioning
confidence: 82%
“…Our current findings demonstrate that, among the analysed miRNA markers, miR‐21 and miR‐375 are the most affected by the NF‐κB inhibitor, underscoring the role of activated NF‐κB with miR‐21 and miR‐375, in promoting acidic bile‐induced cancer‐related molecular alterations in hypopharyngeal cells. There is further evidence that microRNA markers, such as “oncomir” miR‐21 and “tumour suppressor” miR‐375, play a crucial role in initiation and progression of HNSCC 10, 12, 13. Arantes LMRB et al recently reported the fundamental role of miR‐21, as a biomarker, in head and neck carcinogenesis,47 while miR‐375 has been proposed as a predictive biomarker for early diagnosis in laryngeal cancer 48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26] An independent association has been demonstrated between NF-κB activation and upregulation of oncogenic miR-21 and/ or downregulation of the tumor suppressors miR-34a and miR-451a. 7,8 To explore our hypothesis, we performed a pilot study analyzing a group of HSCC specimens and their corresponding adjacent normal tissues (ANTs) derived from patients with documented bile reflux compared with controls to identify possible differences in expression levels of activated NF-κB and related mRNA and miRNA phenotypes. 29 We hypothesized that invasive squamous cell carcinoma derived from patients with documented bile reflux may demonstrate strong NF-κB activation accompanied by messenger RNA (mRNA) and miRNA phenotypes previously identified in murine hypopharyngeal mucosa chronically exposed to acidic bile.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated expression of miR-155 is associated with downregulation of SOCS1 and increased STAT3 expression. The activation of STAT3 can promote the development and differentiation of laryngeal squamous cell carcinoma [33]. This suggests that miR-155 exerts a carcinogenic effect by regulating the expression of the target gene SOCSl-STAT3.…”
Section: Mirnas Promote the Progression Of Laryngeal Cancermentioning
confidence: 99%